2022
DOI: 10.21203/rs.3.rs-1530942/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can the thyme oil be an alternative treatment for human demodicosis?

Abstract: Background: Demodex mites can cause ocular demodicosis in humans. Natural products such as tea tree oil are used for ocular demodicosis, which can take a long time to treat. The aim of our study is to investigate the effects of some essential oils on in vitro mite lifespan. Methods: Eyelashes were examined under a light microscope. Mites were determined and the killing times of mineral oil, tea tree oil, black seed oil, St. John's Wort oil, sage oil and thyme oil were recorded. The active ingredients of thyme,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our findings and previous studies showed strong evidence that essential oil had a potentially effective acaricidal agent for Demodex mite. 11 , 13 , 14 The mechanism of action of essential oils against mites differs from ivermectin and metronidazole. Thai herbal essential oils, especially lemongrass, sweet basil, clove oil, and tea tree oil, should be considered an alternative acaricidal agent against Demodex mites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings and previous studies showed strong evidence that essential oil had a potentially effective acaricidal agent for Demodex mite. 11 , 13 , 14 The mechanism of action of essential oils against mites differs from ivermectin and metronidazole. Thai herbal essential oils, especially lemongrass, sweet basil, clove oil, and tea tree oil, should be considered an alternative acaricidal agent against Demodex mites.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although the efficacies of essential oil against Demodex mites have already been reported, Thai herbal essential oils have yet to be discovered. 11,13,14 For the first time, the current study allowed us to study and compare Thai herbal essential oils, tea tree oil, and metronidazole 0.75%, with ivermectin 1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that different herbal essential oils and their bioactive components of them, especially tea tree oil have great acaricidal efficacy against mites of the Demodex genus ( Demodex folliculorum and Demodex brevis ) in humans ( Gao et al ., 2005 ; Savla et al ., 2019 ; Akkucuk and Kaya, 2022 ). Also, there was just one article that evaluates the in vitro acaricidal effect of tea tree oil as a herbal essential oil on D. canis mites ( Neves et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there was just one article that evaluates the in vitro acaricidal effect of tea tree oil as a herbal essential oil on D. canis mites ( Neves et al ., 2020 ). Despite thyme oil and carvacrol as the most important active ingredients, it was evaluated for the killing of D. folliculorum and D. brevis in humans and shown great and more effective mite killing in comparison with tea tree oil, black seed oil, St. John's Wort oil, and sage oil ( Akkucuk and Kaya, 2022 ). The efficacy of carvacrol against the D. canis has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%